Efficacy of capecitabine-based combination therapy and single-agent capecitabine maintenance therapy in patients with metastatic breast cancer - Lv, Huimin; Yan, Min; Zhang, Mengwei; Niu, Limin; Zeng, Huiai; Cui, Shude (Chinese Journal of Cancer Research, 2014)
Objective: The purpose of this study was to observe the efficacy and toxicities of capecitabine-based chemotherapy and capecitabine monotherapy as maintenance therapy in the treatment of metastatic breast cancer (MBC). Patients and methods: A total of 98 MBC patients were treated with capecitabine combined with vinorelbine (NX). Results: The median number of treatment was 6 cycles (1-7 cycles). There were two cases of complete remission (CR), 58 partial remission, 27 stable disease (SD), 11 progression disease. The overall response rate (ORR) (CR + PR) was 61.2%. The clinical benefit rate (CBR) was 75.5%. Fifty of effective patients received with capecitabine monotherapy as maintenance therapy. The ORR (CR + PR) was 4%. The CBR was 48%. The median progression-free survival (PFS) was 12 months. In maintenance therapy or not, the median post metastasis survival rate (MSR) was 63 and 28 months, respectively. In the combination therapy group, the major grade 3/4 toxicities included hand-foot syndrome (3.1%), skin pigmentation (2.0%), diarrhoea and abdominal distension (5.1%), stomatitis (1.0%), and leukopenia (20.4%). Conclusions: Capecitabine-based combination therapy and single-agent capecitabine maintenance therapy were well tolerated and effective to MBC.